PENGARUH KOMPETENSI, INDEPENDENSI, DAN PROFESIONAL AUDITOR TERHADAP KUALITAS AUDIT - dahlia, Lia; octavianty, Ellyn (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2016)
Audit quality is very important, where the higher the quality audit that is applied to produce financial statements accurate and reliable as a basis for decision making for the users of these financial statements. The purpose of this study was to determine the effect of competence, independence and profeionalisme auditor to audit quality. Processing method to test the validity, reliability, multiple linear regression, hypothesis testing, and test the coefficient of determination. The results showed the competence of auditors in carrying out audits and significant positive effect on audit quality in KAP in South Jakarta. Independence of the auditor in carrying out audits and significant positive effect on audit quality in KAP. While Professionalism auditor in carrying out audits and significant positive effect on audit quality in KAP.Â Keywords: competence, independency, professionalism, and quality audits.Â